2012
DOI: 10.1111/j.1365-2966.2011.20229.x
|View full text |Cite
|
Sign up to set email alerts
|

The 6-GHz methanol multibeam maser catalogue - IV. Galactic longitudes 186°-330° including the Orion-Monoceros region

Abstract: We present the fourth portion of a Galactic plane survey of methanol masers at 6668 MHz, spanning the longitude range 186 • -330 • . We report 207 maser detections, 89 new to the survey. This completes the southern sky part of the methanol multibeam survey and includes a large proportion of new sources, 43 per cent. We also include results from blind observations of the Orion-Monoceros star-forming region, formally outside the latitude range of the methanol multibeam survey; only the four previously known meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
181
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(192 citation statements)
references
References 61 publications
11
181
0
Order By: Relevance
“…6 shows the distributions of integrated flux densities for the 6.7-and 12.2-GHz methanol masers (these values are not available for either the water masers or the excited-state OH masers) and the overall distributions are similar to that of the peak flux densities. The most striking difference in the distributions is the preponderance of 12.2-GHz methanol masers with low integrated flux densities, dominated by a large number of weak, sin- Caswell et al 2010;Green et al 2010;Caswell et al 2011;Green et al 2012;Breen et al 2015), 12.2-GHz methanol (pink; Breen et al 2012aBreen et al ,b, 2014Breen et al , 2016, water (blue; Walsh et al 2014) and excited-state OH masers (orange; Avison et al 2016), and; (bottom) integrated flux density distribution of the 6.7-GHz methanol (magenta; Breen et al 2015) and 12.2-GHz methanol (pink; Breen et al 2012aBreen et al ,b, 2014Breen et al , 2016.…”
Section: Distribution Of Peak and Integrated Flux Densitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…6 shows the distributions of integrated flux densities for the 6.7-and 12.2-GHz methanol masers (these values are not available for either the water masers or the excited-state OH masers) and the overall distributions are similar to that of the peak flux densities. The most striking difference in the distributions is the preponderance of 12.2-GHz methanol masers with low integrated flux densities, dominated by a large number of weak, sin- Caswell et al 2010;Green et al 2010;Caswell et al 2011;Green et al 2012;Breen et al 2015), 12.2-GHz methanol (pink; Breen et al 2012aBreen et al ,b, 2014Breen et al , 2016, water (blue; Walsh et al 2014) and excited-state OH masers (orange; Avison et al 2016), and; (bottom) integrated flux density distribution of the 6.7-GHz methanol (magenta; Breen et al 2015) and 12.2-GHz methanol (pink; Breen et al 2012aBreen et al ,b, 2014Breen et al , 2016.…”
Section: Distribution Of Peak and Integrated Flux Densitiesmentioning
confidence: 99%
“…While the primary target of the survey was the 6.7-GHz methanol maser line, a concurrent survey for 6035-MHz OH masers was also preformed (see Green et al 2009, for a description of the survey or Table 1 for a summary of the survey parameters). In total, 972 methanol masers and 127 excited-state OH masers were detected and are presented in a series of catalogue papers Green et al 2010;Caswell et al 2011;Green et al 2012;Breen et al 2015;Avison et al 2016). Each of the newly discovered 6.7-GHz methanol and excited-state OH masers, together with any known sources that had not been previously observed with an interferometer where subsequently observed with either the ATCA or MERLIN between 2006 and 2014, achieving positional accuracies better than 0.4 arcsec.…”
Section: The Methanol Multbeam (Mmb) Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Minier et al 2003;Xu et al 2008;Breen et al 2013). The Methanol Multibeam survey (MMB; Green et al 2009) completely searched the portion of the Galactic plane accessible to the Parkes 64-m radio telescope, detecting a total of 972 masers across the total longitude range of 186 • (through the Galactic Centre) to 60 • within latitudes of ±2 • Green et al 2010;Caswell et al 2011;Green et al 2012;Breen et al 2015). The MMB catalogues present the precise positions for each of the 6.7-GHz methanol masers that were either taken from the literature, or derived from new Australia E-mail: Shari.Breen@csiro.au † Deceased 2015 January 14.…”
Section: Introductionmentioning
confidence: 99%
“…The Methanol Multibeam (MMB) survey (Green et al 2009) has identified 703 methanol masers between 186 • < ℓ < 20 • and |b| < 2 • with a further 4 masers being found towards the OrionMonoceros Complex (Green et al 2012). The full published catalogue therefore consists of 707 methanol masers Green et al 2010;Caswell et al 2011;Green et al 2012). Distances have been determined for the majority of these masers from the radial velocity of the strongest intensity maser component and the Reid et al (2009b) Galactic rotation model.…”
mentioning
confidence: 99%